2004
DOI: 10.1016/s0092-8674(03)01027-4
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanism of Hsp90 Regulation by the Protein Kinase-Specific Cochaperone p50cdc37

Abstract: Recruitment of protein kinase clients to the Hsp90 chaperone involves the cochaperone p50(cdc37) acting as a scaffold, binding protein kinases via its N-terminal domain and Hsp90 via its C-terminal region. p50(cdc37) also has a regulatory activity, arresting Hsp90's ATPase cycle during client-protein loading. We have localized the binding site for p50(cdc37) to the N-terminal nucleotide binding domain of Hsp90 and determined the crystal structure of the Hsp90-p50(cdc37) core complex. Dimeric p50(cdc37) binds t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
376
2
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 319 publications
(397 citation statements)
references
References 61 publications
18
376
2
1
Order By: Relevance
“…Comparison with Hsp90 -Although both GRP94 and Hsp90 bind ATP/ADP, the conformation of nucleotide-bound GRP94 differs from that of any of the previously determined structures of Hsp90 (6,8,9,11,35,37). As seen from the superposition in Fig.…”
Section: Grp94-atp Structurementioning
confidence: 82%
“…Comparison with Hsp90 -Although both GRP94 and Hsp90 bind ATP/ADP, the conformation of nucleotide-bound GRP94 differs from that of any of the previously determined structures of Hsp90 (6,8,9,11,35,37). As seen from the superposition in Fig.…”
Section: Grp94-atp Structurementioning
confidence: 82%
“…Our data and previous studies may explain the sequence of chaperoning cycles in Hsp90 superchaperone complex. The previous results have shown that the COOH terminus of Cdc37 inserts into the ATP-binding pocket of Hsp90 (open state), later ATP binding to Hsp90 ejects Cdc37 from Hsp90 (14), setting up the stage for binding of p23 to Hsp90. Therefore, Cdc37 and p23 bind to Hsp90 at different stages of the chaperoning cycle without coexisting in one complex.…”
Section: Discussionmentioning
confidence: 95%
“…The recent structural study of Hsp90/Cdc37 has shown that Cdc37 binds to the NH 2 -terminal domain of Hsp90 by inserting its COOHterminal side chain into the nucleotide-binding pocket, holding Hsp90 in an ''open'' conformation (14). Therefore, progression from this stage through the ATPase cycle requires the ejection of Cdc37 side chain from the binding pocket (14). In vitro protein binding analysis also suggests that binding of Cdc37 and p23 to Hsp90 is mutually exclusive and the p23-Hsp90-Cdc37 complex could not exist (24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides the known Hsp90 partners, two tetratricopeptide repeat (TPR)-domain-containing proteins, Ttc1 and FLJ21908, were isolated with immobilized Hsp90CT, which was consistent with the design of the assay. Although the use of Hsp90CT excludes the specific isolation of Cdc37, which binds to the N-domain of Hsp90 (Roe et al 2004), immunoprecipitation also failed to isolate Cdc37 (Te et al 2007). Notably, Falsone et al could not coimmunoprecipitate Cdc37, which may have resulted from overlapping binding sites of the antibody and Cdc37 on Hsp90 (Falsone et al 2005).…”
Section: Discussionmentioning
confidence: 99%